2020
DOI: 10.1038/s41598-020-74636-2
|View full text |Cite
|
Sign up to set email alerts
|

CDCA7 and HELLS suppress DNA:RNA hybrid-associated DNA damage at pericentromeric repeats

Abstract: Immunodeficiency, centromeric instability, facial anomalies (ICF) syndrome is a rare autosomal recessive disorder that is caused by mutations in either DNMT3B, ZBTB24, CDCA7, HELLS, or yet unidentified gene(s). Previously, we reported that the CDCA7/HELLS chromatin remodeling complex facilitates non-homologous end-joining. Here, we show that the same complex is required for the accumulation of proteins on nascent DNA, including the DNMT1/UHRF1 maintenance DNA methylation complex as well as proteins involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Therefore, we asked whether the DNA hypomethylation of pericentromeric repeats in ZBTB24 KO, CDCA7 KO, and HELLS KO cells causes chromosome instability via similar process. Consistent with the hypomethylation state of the repeats, the transcription and formation of aberrant DNA:RNA hybrids at the repeats were significantly increased in ZBTB24 KO, CDCA7 KO, and HELLS KO cells (Unoki et al., 2019 , 2020 ). Since it is reported that DNA:RNA hybrids and R‐loops are poor substrates for DNMT1 (Ross et al., 2010 ), this may accelerate loss of methylation at the repeats in these KO cells.…”
Section: Dna Methylation and Chromosome Stabilitymentioning
confidence: 73%
See 4 more Smart Citations
“…Therefore, we asked whether the DNA hypomethylation of pericentromeric repeats in ZBTB24 KO, CDCA7 KO, and HELLS KO cells causes chromosome instability via similar process. Consistent with the hypomethylation state of the repeats, the transcription and formation of aberrant DNA:RNA hybrids at the repeats were significantly increased in ZBTB24 KO, CDCA7 KO, and HELLS KO cells (Unoki et al., 2019 , 2020 ). Since it is reported that DNA:RNA hybrids and R‐loops are poor substrates for DNMT1 (Ross et al., 2010 ), this may accelerate loss of methylation at the repeats in these KO cells.…”
Section: Dna Methylation and Chromosome Stabilitymentioning
confidence: 73%
“…Second, we identified the proteins that are less accumulated on newly synthesized DNA strands in the absence of CDCA7 by isolation of proteins on nascent DNA (iPOND)‐MS/MS analysis using asynchronized wild‐type and CDCA7 KO HEK293 cells. We found that the accumulation of DNMT1 and UHRF1 on newly synthesized strands was reduced by approximately 50% and 40%, respectively, in CDCA7 KO cells (Unoki et al., 2020 ), suggesting that the CDCA7/HELLS complex is required for access of the DNMT1/UHRF1 complex to approximately half of newly synthesized strands. Considering that the CDCA7/HELLS complex is plausibly required for replication‐uncoupled maintenance DNA methylation (Figure 1b ), this result is reasonable.…”
Section: Chromatin Remodeling In Replication‐uncoupled Maintenance Dn...mentioning
confidence: 88%
See 3 more Smart Citations